PERSEPSI PETANI PADI TENTANG INOVASI PENGELOLAAN TANAMAN TERPADU (PTT) PADI SAWAH DAN TINGKAT PENERAPANNYA - Desi Maharani Agustini (MADURANCH: Jurnal Ilmu Peternakan, 2013)
Research objectives were : (1) to descripe the farmer’s perception of Paddy Crop Integrated Management and its Implementation (2) to analyse correlation betwen farmer’s characteristic and their perception of Paddy Crop Integrated Management (3) to analyse correlation between farmer’s perception and the implementation of ICM. The study was conducted in the District Pamekasan, determining tehe location using purposive sampling technique. A number of 42 farmers were collected as respondents. To obtain data, both primary data and secondary data conducted by: interview, directly to the respondent farmer’s using a list of questions’s that havebeen organized and structured interview by using questionnare, observation for obtain about the state of the area to be examined by conducting surveys. To analyse the first goal using desciptiptive analytical, the second purpose is analyse correlation betwen farmer’s characteristic and their perception of Paddy Crop Integrated Management with chi square analysis, the third purpose is analyse correlation between farmer’s perception and the implementation of ICM with chi square analysis. The research results showed that respondents had enough information about ICM paddy. But for the farmer’s perception about BWD is too short. The level implementation of ICM paddy in pamekasan district was enougt high. The relationship betwen farmer’s characteristic and their perception of ICM paddy was correlate. The strong correlate was age, non formal education, and farmer’s income. The farmer’s perception abaout using BWD had strong correlate with the level implementation of BWD.